2016
DOI: 10.1371/journal.pone.0165654
|View full text |Cite
|
Sign up to set email alerts
|

CDH1 Missense Variant c.1679C>G (p.T560R) Completely Disrupts Normal Splicing through Creation of a Novel 5’ Splice Site

Abstract: Disease-causing germline mutations in CDH1 cause Hereditary Diffuse Gastric Cancer (HDGC). For patients who meet the HDGC screening criteria, the identification and classification of the sequence variants found in CDH1 are critical for risk management of patients. In this report, we describe a germline CDH1 c.1679C>G (p.T560R) variant identified in a 50 year old man who was diagnosed with gastric cancer with a strong family history of gastric cancer (one living brother was diagnosed with gastric cancer at 63 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…The results so far described here support the conclusion that c.277 + 2 T > G in HSD17B3 and c.544 G > A in SRD5A2 potentially disrupt binding of U1snRNP to the 5′ splice site therefore inhibiting splicing initiation 29 , 30 . These mutations highlight the importance of a conserved 5′ splice site sequence for correct binding of U1 snRNP and spliceosome machinery assembly, and show that disruption of this process may result in human disease 30 , 31 .…”
Section: Discussionsupporting
confidence: 87%
“…The results so far described here support the conclusion that c.277 + 2 T > G in HSD17B3 and c.544 G > A in SRD5A2 potentially disrupt binding of U1snRNP to the 5′ splice site therefore inhibiting splicing initiation 29 , 30 . These mutations highlight the importance of a conserved 5′ splice site sequence for correct binding of U1 snRNP and spliceosome machinery assembly, and show that disruption of this process may result in human disease 30 , 31 .…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, this variant had been reported twice before in the literature-in a young patient with DGC [5] and in a family of Indian origin also with DGC [6]-together with two unpublished cases reported to the Institute of Molecular Pathology and Immunology of the University of Porto (IPATIMUP; personal communication from R Seruca, 2016). Benusiglio et al did not perform any type of functional analysis [5], while Yelskaya et al described that the c.1679C>G variant disrupts normal splicing, which presumably leads to truncation of the protein [6]. In support of these findings, we also observed that the c.1679C>G change generates an alternative 5′ splice site, leading to the loss of 32 nucleotides in exon 11 or to a premature stop codon at position 576 of the protein.…”
Section: Discussionsupporting
confidence: 84%
“…The haplotype study indicated that a common ancestry of this variant event for the three families is unlikely. This result was expected for two reasons: (1) a large region of CDH1 (which includes our variant site) shows no linkage disequilibrium (GTEX), which suggests it might be very exposed to recombination; and (2) there are other individuals reported to carry this variant who have very distant geographic origins [5,6].…”
Section: Discussionmentioning
confidence: 75%
“…Table S1.To avoid double counting of evidence, this PP3 rule cannot be used for canonical splice site variants and should only be applied to splicing variants at locations other than the ±1/2 positions. Note, this code also does not apply to the last nucleotide of exon 3 (c.387G) (Yelskaya, et al, 2016).…”
Section: Resultsmentioning
confidence: 99%